Curves in homogeneous spaces and their contact with 1-dimensional orbits - do Nascimento, Vanderlei M. [UNESP]; Saeki, Osamu (Springer, 2011)
Let alpha be a C(infinity) curve in a homogeneous space G/H. For each point x on the curve, we consider the subspace S(k)(alpha) of the Lie algebra G of G consisting of the vectors generating a one parameter subgroup whose orbit through x has contact of order k with alpha. In this paper, we give various important properties of the sequence of subspaces G superset of S(1)(alpha) superset of S(2)(alpha) superset of S(3)(alpha) superset of ... In particular, we give a stabilization property for certain well-behaved curves. We also describe its relationship to the isotropy subgroup with respect to the contact element of order k associated with alpha.
Keywords: Contact; Homogeneous space; Lie group; 1-parameter subgroup; Lie algebra